2011
DOI: 10.1536/ihj.52.65
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparison of Clinical and Angiographic Outcomes After Sirolimus-Eluting and Bare-Metal Stent Implantation in 312 Consecutive, Nonrandomized Severely Calcified Lesions Using a Rotablator

Abstract: SummaryIn order to compare the long-term clinical and angiographic outcomes after sirolimus-eluting stent (SES) and baremetal stent (BMS) placement in severely calcified lesions using a rotablator under the widespread indication of SES, a nonrandomized examination of 312 consecutive lesions after successful implantation of a BMS (99 lesions in 84 patients; from January 2003) or SES (213 in 167; from September 2004) using a rotablator was conducted. The lesionbased primary endpoints (cardiac death and nonfatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Several studies have showed that DES implantation after RA reduced the incidences of TLR 21) and MACE. 16,17) Mezilis, et al reported that a combined strategy consisting of RA and DES reduced the rate of MACE combined with TLR, TVR, stroke, MI, and occurrence of death in 150 patients with heavily calcified coronary artery lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that DES implantation after RA reduced the incidences of TLR 21) and MACE. 16,17) Mezilis, et al reported that a combined strategy consisting of RA and DES reduced the rate of MACE combined with TLR, TVR, stroke, MI, and occurrence of death in 150 patients with heavily calcified coronary artery lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the signi cant reduction of restenosis by Drug-eluting stent DES , several factors including diabetes, hemodialysis, and severe calci cation have been reported to be high-risk factors for restenosis after DES implantation [14][15][16][17][18][19][20] . Several studies have shown that DES implantation after the use of Rota reduced in the incident of target lesion revascularization TLR 21 and major adverse cardiac events [22][23][24] . It is that lesion modi cation by the Rota could yield smooth stent delivery, prevent damage to the polymer coating 25 , and provide optimal stent expansion, all of which could help DES be effective, even for calci ed lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was a lesion-based, retrospective, nonrandomized, single-center study, as largely determined by a historical comparison with the outcomes of BMS in our previous reports (6,7). The rationale of almost unrestricted use of SES has been previously reported (2,(5)(6)(7).…”
Section: Populationmentioning
confidence: 99%
“…The rationale of almost unrestricted use of SES has been previously reported (2,(5)(6)(7). From January 2003 to August 2004 (before SES was approved in Japan), BMS was electively, exclusively, and successfully placed in 519 de novo native coronary lesions, excluding patients over the age of 80 years and those with prior coronary artery bypass grafts (CABG).…”
Section: Populationmentioning
confidence: 99%